Twórczość literacka współczesnych polskich migrantek jako materiał glottodydaktyczny .......... 125 - Zych, Justyna (Kultura i literatura w glottodydaktyce polonistycznej wobec wymagań rzeczywistości, 2025)
CONTEMPORARY POLISH FEMALE MIGRANTS’ WRITING AS TEACHING MATERIAL FOR POLISH AS A FOREIGN LANGUAGE CLASSThe article explains in detail why it is worth addressing the topic of migration in Polish as a foreign language classes. The author claims that it is a current, socially significant issue that directly relates to the students’ experiences and therefore has the potential to engage them during classes. The author also argues that an effective strategy for introducing the complex topic of migration in class is to present selected excerpts from contemporary prose written in Polish by Polish migrant women. The article includes ideas of classroom activities based on the chosen excerpts from three contemporary works that belong to migration literature: an autobiographical novel Wilcza rzeka (Wolf River, 2021) by Wioletta Grzegorzewska, a novel of manners Nielagalne związki (Illegal Liaisons, 2010) by Grażyna Plebanek, and a collection of short stories Imigracje (Immigrations, 2011) by Kaja Malanowska.